A ação católica em arquivos eclesiásticos da Arquidiocese de Santa Maria RS: articulação da igreja com os leigos e o estado (décadas de 1930-1940) - Silva, Rosani Beatriz Pivetta da (2023)
This doctoral thesis is linked to the Memory and Cultural Heritage Research Area of the PPGH at UFSM. It aims to analyze the memory of the ecclesiastical movement Ação Católica in the Archdiocese of Santa Maria (RS), from 1930 to 1945, which concerns the strategies developed by social agents of the Catholic Church, who aimed, through social catholicism to find new roles for lay people in the context of the Church.The focus is about the performance of the Catholic clergy and the role of the ecclesiastical assistant, who exercised intellectual, moral and administrative authority in the organization of the lay people. The Catholic Church wanted to revitalize the hegemony of Catholicism, which historically had social, political and economic prominence in Brazilian history. To this end, we mapped the parishes that are part of the Archdiocese of Santa Maria, which are thirty-nine (39), in an area of 20.263 km², which indicates the scope of the research theme. Nineteen (19) parishes were selected for the research, because they hypothetically hold documents relating to Catholic Action, in the period defined in this study. Thus, three (03) parishes are located in Santa Maria and sixteen (16) are located in other cities in Rio Grande do Sul state. The parishes of Santa Maria are: Metropolitan Cathedral parish, Nossa Senhora da Conceição parish; Nossa Senhora das Dores parish and Santa Catarina parish. In the region covered by the Archdiocese, we highlight the parishes in the cities of: Cacequi, founded in 1935; Nova Palma (1919); Júlio de Castilhos (1883); São Sepé (1850); Vale Vêneto (1911); Jaguari (1915); Silveira Martins (1884); Ivorá (1918); São Vicente do Sul (1876); Dona Francisca (1934); Arroio Grande (1919); São Pedro do Sul (1882); Pinhal Grande (1942); Restinga Seca (1939); Tupanciretã (1920) and Formigueiro, in 1938. This research indicates the potential of the theme, since the records of the Catholic Action movement in the Archdiocese of Santa Maria inform how much the Archdiocese's articulations were in line with the policies of the Roman Church, highlighting civility, morality and the fight against the enemies of Church. These themes can contribute to understanding the influence of Catholic and religious social agents in the history of Rio Grande do Sul. The methodological strategy was developed based on documentary and bibliographic research and content analysis. Among the research results, we highlight the significant organization of lay people, to contribute to the appreciation and dissemination of the principles proclaimed by the Roman Apostolic Catholic Church.